Manhaj Muqtarah Li Ta`limi Maharat Al Qiraah Li Al Mustawa Al Mutaqaddim Min Khilali Al Qashash Al Qurani Qishshatu Musa Alaihi As Salam Namudzajan - Sa’adiyah Ratnasari Sagala; Husnul Khatimah; Huriyatul Jannah (Ukazh: Journal of Arabic Studies, 2021)
لقد انتشر كثير من المناهج التعليمية لتعليم اللغة العربية مع أنواعها المختلفة في هذا العصر. فبناء على هذا أرادت الباحثة أن تساهم في تطوير المناهج التعليمية لتعليم اللغة العربية بإصدار بحثها بعنوان: (منهج مقترح لتعليم مهارة القراءة للمستوى المتقدم من خلال القصص القرآني "قصة موسى عليه السلام" نموذجا). هدف هذا البحث معرفة منهج مقترح لتعليم مهارة القراءة للمستوى المتقدم من خلال القصص القرآني (قصة موسى عليه السلام نموذجا)، ومعرفة كيفية الاستفادة من تلك القصص بوضعها منهجا مقترحا لتعليم مهارة القراءة للمستوى المتقدم. وهذ البحث هو البحث النوعي على المنهج الوصفي التحليلي وهو أسلوب من أساليب التحليل المركز على معلومات كافية ودقيقة عن ظاهرة أو موضوع محدد في فترة زمنية معلومة، وذلك من أجل الحصول على نتائج علمية، ثم تفسيرها بطريقة موضوعية بما ينسجم مع المعطيات الفعلية الظاهرة. فقامت الباحثة بتتبع المعلومات حول منهج مقترح وتعليم مهارة القراءة والقصص القرآني وبالخاصة قصة نبي الله موسى عليه السلام ثم جمعها، وتصنيفها، وعرضها، والأخير الاستنتاج. فبعد تمام البحث حصلت الباحثة على أن منهج مقترح لتعليم مهارة القراءة للمستوى المتقدم من خلال قصة موسى عليه السلام يحتوي على خمسة عناصر أساسية هي الأهداف، والمحتوى، وطريقة التعليم، ووسائل التعليم، والتقويم. وتمت الاستفادة من قصة موسى عليه السلام بوضعها في النصوص القرائية والتدريبات للنص وألعاب اللغوية المتعلقة بالنص في تعليم مهارة القراءة للمستوى المتقدم. There are many educational curriculums for teaching Arabic with various types in this era. Based on this, researchers want to contribute to the development of an educational curriculum for teaching Arabic by publishing his research entitled: (proposed methode to teach reading skill to the advanced level through Quranic stories "The Story of Musa, peace be upon him," as an example). The purpose of this study is to find out the proposed curriculum to teach reading skills to an advanced level through the Qur'anic stories (the story of Moses, peace be upon him as a model), and to find out how to benefit from these stories (the story of Moses, peace be upon him as a model) by developing a recommended approach to teach reading skills to an advanced level. This research is qualitative research with a descriptive analysis method, an analytical method that focuses on sufficient and accurate information about a phenomenon or topic certain in pe period time that is known, to obtain scientific results, and then interpret them objectively according to the actual data displayed. Researchers trace information about the proposed curriculum and teaching reading skills and Qur'anic stories, especially the stories of the Prophet Allah, Musa, peace be upon him, then collected ,classified presented, and the conclusions. After completing the research, researchers found that the curriculum proposed to teach reading skills to the advanced level through the Qur'anic stories (the story of Moses, peace be upon him) as a model) contained five basic elements: objectives, content, methods education, teaching methods, and evaluation. The story of Musa, peace be upon him, was used by placing it in reading texts, text exercises and language games related to text in teaching reading skills to an advanced level.